The State of the World's Midwifery 2021 - United Nations Population Fund (United Nations, 2021)
Sexual, reproductive, maternal, newborn and adolescent health (SRMNAH) is an essential component of the Sustainable Development Goals (SDGs). Despite a steady drop in maternal and newborn deaths since 1990, hundreds of thousands of women and newborns around the world continue to die each year during pregnancy and childbirth: an estimated 289,000 women and about 3 million newborn babies died in 2013 alone. The vast majority of loss of life is due to complications and illnesses that could be prevented with proper antenatal care and the presence of a skilled midwife during delivery. In recognition of the need to improve such realities and overall SRMNAH, this publication focuses on the availability, accessibility, acceptability and quality of midwifery services and the pivotal role midwifes play within the wider SRMNAH workforce.